On the effect of tastant excluded fillers on sweetness and saltiness of a model food - Goh, Aaron; Leroux, B.; Groeneschild, C.; Busch, J. (Wiley-Blackwell Publishing, Inc., 2010)
In this study, the effect on taste due to the addition of air bubbles to a water-based gel was investigated. The gel phase contained either sucrose to give a sweet taste or sodium chloride to give a salty taste. For the sweet gels, taste intensities were evaluated for samples with different volume fractions of the air bubbles (up to 40%, v/v) and different concentrations of the sucrose. For the salty gels, samples were evaluated at 40% volume fraction of air bubbles. It was found that a reduction of the sodium chloride or sucrose by the same weight percentage as the volume fraction of the air bubbles in the samples gave equal taste perception as the nontastant-reduced samples. Moreover, saltiness and sweetness perception were clearly enhanced at 40% volume fractions of air bubbles if the sodium chloride or sucrose was not reduced. Thus, the overall tastes of the samples appeared to depend mainly on the concentration levels of the salt or the sucrose in the aqueous phase irrespective of the volume fraction of the air bubbles. However, the air bubbles were found to change the texture and appearance of the samples. It has been demonstrated that the inclusion of air bubbles offers scope for the reduction of sodium chloride or sucrose in food products.